Error Analysis of Learner in Solving Problem in Mathematics Course Based on Newman Error Analysis (NEA) - Ekasari, Aprilita; Putra, Don Jaya (Universitas Negeri Malang, 2024)
The purpose of this research is to identify learner errors in problem-solving within the mathematics course, particularly in the subtopic of integration, based on Newman's Error Analysis (NEA). The subjects of this research were 14 first-year learners from the Physics Education Department at Musamus University, Merauke. The research method employed in this study is descriptive with a qualitative approach. The instruments used in this research were tests and interviews. The test questions were used to measure the errors made by learners according to Newman's framework. Furthermore, four subjects were selected as participants for interviews to analyze the difficulties encountered while solving problems that led to learner errors. The results of this study revealed the presence of comprehension errors, transformation errors, process errors, and encoding errors when learners solved problems related to the subtopic of integration